(2R)-2-Benzenesulfonamido-2-phenylethanoic acid - Arshad, Muhammad Nadeem (International Union of Crystallography, 2009)
In the title compound, C(14)H(13)NO(4)S, the dihedral angle between the aromatic ring planes is 45.52 (18)°. In the crystal structure, intermolecular N—H⋯O and O—H⋯O hydrogen bonds lead to chains of molecules propagating in [100] in which the the ring motifs R (2) (1)(8), R (2) (2)(8) and R (3) (3)(11) are apparent. These polymeric chains are linked through C—H⋯O interactions.